Enhancing Student Performance Classification Through Dimensionality Reduction and Feature Selection in Machine Learning - Mustakim Mustakim; Windy Junita Sari; Fara Ulfa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Education plays an important role in shaping the intellectual and character of the nation's next generation. However, poor student academic performance is a major challenge, especially regarding student retention and dropout risk. This study aims to evaluate the performance of machine learning algorithms, namely K-Nearest Neighbor (K-NN), Light Gradient Boosting Machine (LightGBM), and Extreme Gradient Boosting (XGB), and analyze the effect of dimensionality reduction using Principal Component Analysis (PCA) and feature selection with Recursive Feature Elimination (RFE) on student performance prediction accuracy. The research dataset consists of 395 student samples with demographic, social, and academic attributes. The results show that XGB has the best performance with 98.32% accuracy and can predict all classes with perfect 100% accuracy. LightGBM and K-NN achieved 94.87% and 93.88% accuracy, respectively. The best attributes affecting student performance were found in the “Highly Prioritized” category, including study time, family support, family, and health. Although PCA slightly degraded the model performance, feature selection with RFE significantly improved accuracy. This study concludes that proper algorithm selection and focus on relevant attributes can improve prediction accuracy and efficiency, making an important contribution to the development of more effective education prediction systems.